Inflammatory responses associated with hyposaline stress in gill epithelial cells of the spotted scat Scatophagus argus. Issue 114 (July 2021) - Zhong, Yong; Duan, Zhengyu; Su, Maoliang; Lin, Yanquan; Zhang, Junbin
Abstract: The molecular processes of immune responses in mucosal tissues such as fish gills under environmental stress are poorly understood. In the present study, pro-inflammatory response under hyposaline stress and its regulation by cortisol/corticosteroid receptors (CRs) in gill epithelial cells of the spotted scat Scatophagus argus were analyzed. The fish were transferred to freshwater for 6 days (144 h) of acclimation. Following freshwater exposure, the cortisol concentration increased transiently before returning to the control level over time. mRNA expression of pro-inflammatory cytokines (TNF-a, IL-1b and IL-6) was stimulated by cortisol through CR signals at early stages of acclimation, but hyposaline stress inhibited their levels by the end of the experimental period. The transcriptional profile of anti-inflammatory cytokine IL-10 was quite different from these pro-inflammatory cytokines, and its value fluctuated within a narrow range during the experimental period. Full-length cDNAs of mineralocorticoid receptor (MR) and glucocorticoid receptor 1 (GR1) (different kinds of CRs) were cloned from the gills. Our results showed that MR and GR displayed mutually antagonistic effects during hyposaline stress. MR responded quickly at early stages, and its expression decreased with the drop of cortisol concentration. By contrast, GR expression was maintained at high levels after the acclimation of freshwater exposure. The tight coordination of GR and MR helps to shape the effects of stress on the immune system, which in turn, regulates the stress response. Our results confirm the interaction between endocrine and cytokine messengers and a clear difference in the sensitivity of GR and MR during the hyposaline challenge in gill epithelial cells of the spotted scat Scatophagus argus . Highlights: Gill epithelial cells of Scatophagus argus were isolated and purified. MR and GR displayed mutually antagonistic effects during hyposaline stress. mRNA abundances of TNF-α, IL-1β, and IL-6 were tightly associated with MR and GR signals. Pro-inflammatory response was ignited by environmental stress, and suppressed after longer exposure to freshwater.